The Effect of STEM-Based Robotic Applications on the Creativity And Attitude of Students - Aydın Tiryaki; Sibel Adıgüzel (Journal of Science Learning, 2021)
In the present study, the effects of STEM based robotics applications on students' creativity and scientific attitudes in the Electricity Unit of 7th grade have been investigated by using the nested pattern of the mixed method. Sixty students, 30 of whom are the experimental group and the other 30 constitute the control group, attending a post-school course in Istanbul  in the academic year of 2018-2019, participated 2 weeks of pre-applications and 4 weeks of applications. TOSRA,to measure attitude towards science, and “Torrance Creative Thinking Test”,to measure creativity, were applied as pre and posttest. The data gained from the tests were analyzed with SPSS 21. Semi-structured interviews' data were analyzed by using content analysis. As a result, it was observed that STEM based robotics applications significantly increased students' creativity and attitudes towards science. Interview findings show that students enjoy using STEM applications that contain applications instead of theoretical knowledge. Using robotic and complex software materials to solve daily life problems, they felt like scientists during the practices and the applications affected their future career choices.Keywords STEM; creativity; robotic application; attitude; TOSRA